2014
DOI: 10.1371/journal.pone.0100445
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic-Like Neurons Derived from Oral Mucosa Stem Cells by Developmental Cues Improve Symptoms in the Hemi-Parkinsonian Rat Model

Abstract: Achieving safe and readily accessible sources for cell replacement therapy in Parkinson’s disease (PD) is still a challenging unresolved issue. Recently, a primitive neural crest stem cell population (hOMSC) was isolated from the adult human oral mucosa and characterized in vitro and in vivo. In this study we assessed hOMSC ability to differentiate into dopamine-secreting cells with a neuronal-dopaminergic phenotype in vitro in response to dopaminergic developmental cues and tested their therapeutic potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 62 publications
(63 reference statements)
0
33
0
Order By: Relevance
“…Isolation and enrichment of neural progenitors and NC-derived cells has been classically performed with cells enzymatically released directly from the tissue, and then culturing them in suspension in a serum-free medium supplemented with mitogens where cells aggregate to form floating spheres (also called neurospheres) (Gil-Perotin et al, 2013;Pastrana et al, 2011). This protocol may selectively enrich a distinct cell population from the tissue or allow the cells to maintain or acquire a distinct phenotype that might be lost during the standard culture of plasticadherent cells in serum containing medium (Pastrana et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolation and enrichment of neural progenitors and NC-derived cells has been classically performed with cells enzymatically released directly from the tissue, and then culturing them in suspension in a serum-free medium supplemented with mitogens where cells aggregate to form floating spheres (also called neurospheres) (Gil-Perotin et al, 2013;Pastrana et al, 2011). This protocol may selectively enrich a distinct cell population from the tissue or allow the cells to maintain or acquire a distinct phenotype that might be lost during the standard culture of plasticadherent cells in serum containing medium (Pastrana et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Lineage-tracing of NC-derived cells in juvenile transgenic Wnt1-reporter mice gingiva has indicated that majority of connective tissue cells also in gingiva are of NC origin (Xu et al, 2013), but it is unclear if these cells are retained during aging in vivo. Additionally, in standard cultures of human gingival connective tissue cells, a large proportion of cells have been reported to express neural and NC-related genes, including nestin and p75 low-affinity neurotrophin receptor (p75NTR), and possess both mesodermal and neurogenic differentiation capacity when appropriately stimulated (Ganz et al, 2014;Marynka-Kalmani et al, 2010). Thus, gingival connective tissue may contain NC-derived cells, but their NC-related properties have not been characterised in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Dental pulp was considered as a convenient source of SC, yet in order to harvest SC from the pulp, tooth vitality is irreparably damaged or the tooth needs to be extracted. The regenerative ability of nasal mucosa stem cells has been recently well proven: in a parkinsonian rat model (Müller et al., ), in an hemi‐parkinsonian rat model (Ganz, Arie, Buch, et al.s, ) and in a spinal cord injury model (Cho et al., ). Moreover, hOMSC in an experimental rat model of sciatic nerve injury revealed a neuroprotective effect, improving the motor function following transplantation (Ganz, Arie, Ben‐Zur, et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the excellent potential of hOMSC has been shown by the fact that they can differentiate towards ectodermal, mesodermal and endodermal cell lineages (Marynka‐Kalmani et al., ). hOMSC transplanted into various neural damage mouse models resulted in clinical improvement and possible regeneration of the neural tissue (Cho et al., ; Ganz, Arie, Buch, et al.s, ). As hOMSC are very promising candidates for transplantation in the mouse model of brain ischaemia, in which regenerative process includes reactivation of neurogenesis, the main aim of this study was to perform the analyses by observing interactions between hOMSC and mNSC cell populations in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Later, it has been demonstrated that some soluble factors involved in the development of DA neurons induced a DA phenotype in human oral mucosa stem cells (hOMSCs) in vitro that significantly improved the motor function of hemiparkinsonian rats. Immunofluorescence analysis of specific DA marker of naive and differentiated hOMSCs showed that 35% and 82% were positive for TH respectively [65].…”
Section: Mesenchymal Stem Cells (Mscs)mentioning
confidence: 99%